Feeding ecology of the beach silverside Atherinella blackburni (Atherinopsidae) in a tropical sandy beach, Southeastern Brazil - Gonzalez, Julio Guazzelli [UNESP]; Vaske Junior, Teodoro [UNESP] (Inst Oceanografico, Univ Sao Paulo, 2017)
The feeding ecology of the beach silverside (Atherinella blackburni) in the surf zone of a tropical sand beach, located in the southeastern Brazil, was accessed through the gut content analysis of 198 fish. Factors such as fish's size, season and day period were analysed to understand how these variables affect the diet composition of the species. Results show that A. blackburni is a coastal neritic fish with a broad feeding niche. Most recurrent prey were zooplanktonic crustaceans, insects and benthic molluscs, in which Copepoda crustaceans were the dominant dietary item in occurrence and abundance. A. blackburni appears to have a slight ontogenetic shift in its diet, changing from benthic molluscs to crustaceans and insects along its life cycle. The diel activity also reveals to be an important factor to the A. blackburni feeding ecology. The predominant occurrence of small fish during the morning, along with the main preys for this size class, suggests that small individuals use shallower waters as feeding grounds during the morning and, during the night, they move to deeper waters for protection against predators.
Keywords: Diel activity; Diet; Ontogenetic shift; Resources partitioning; Surf zone; Zooplanktivorous